Implementing a Digital Hub Strategy: Preservice Teacher and Faculty Perspectives (LEARNing Landscapes, 2018)
An education professor and a preservice teacher candidate describe their respective insights on the design and implementation of the first iteration of an open, web-based professional portfolio project. The student’s lived experience shows that for some, a Digital Hub can be a useful tool for curation, reflection, and networking; survey data suggests that not all students see value in this work, however. The pedagogical, programmatic, and research implications of this project are discussed.
Keywords: web-based professional portfolio; preservice teacher education; student perspectives; professor perspectives; survey